2011
DOI: 10.1007/s12630-011-9560-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of intravenous ketamine for postoperative analgesia

Abstract: Purpose Perioperative intravenous ketamine may be a useful addition in pain management regimens. Previous systematic reviews have included all methods of ketamine administration, and heterogeneity between studies has been substantial. This study addresses this issue by narrowing the inclusion criteria, using a random effects model, and performing subgroup analysis to determine the specific types of patients, surgery, and clinical indications which may benefit from perioperative ketamine administration. Source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
327
3
22

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(362 citation statements)
references
References 72 publications
10
327
3
22
Order By: Relevance
“…44 It has also been shown that ketamine was able to reduce the socalled OIH 34 for 48 hr after major laparotomy without epidural analgesia. The most common regimen for intravenous administration of ketamine was 0.2-0.5 mgÁkg -1 at the induction of anesthesia, followed by half the bolus dose every hour and none during the last hour of surgery.…”
Section: Ketaminementioning
confidence: 99%
See 1 more Smart Citation
“…44 It has also been shown that ketamine was able to reduce the socalled OIH 34 for 48 hr after major laparotomy without epidural analgesia. The most common regimen for intravenous administration of ketamine was 0.2-0.5 mgÁkg -1 at the induction of anesthesia, followed by half the bolus dose every hour and none during the last hour of surgery.…”
Section: Ketaminementioning
confidence: 99%
“…44 Il est aussi démontré que la kétamine peut réduire l'OIH 34 pendant les 48 h suivant une laparotomie majeure en l'absence de péridurale. Le régime d'administration intraveineuse le plus commun pour la kétamine est: 0,2 à 0,5 mgÁkg -1 à l'induction de l'anesthésie, puis la moitié de cette dose bolus toutes les heures, à cesser une heure avant la fin de la chirurgie.…”
Section: Kétamineunclassified
“…Ketamine is a non-competitive NMDA receptor antagonist with hypnotic and analgesic activity, which can be administrated in many ways (5) .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 We report the pain management of a patient with ischemic limb pain using an ultra-low-dose ketamine infusion.…”
Section: To the Editormentioning
confidence: 99%